Automobile’s role in the future of transportation system: Tehran as an example - Riahi, Manochebr (Proceedings from the Annual Transport Conference at Aalborg University, 1996)
Housing is among the most important problems. There are two different alternatives regarding the human settlement planning in the large cities: If no formula is devised to cope with this problem, the centre of the city and some city quarters will become slum areas or twilight zones. If houses are built in a hurry and without adequate study, then the unplanned and uncontrolled development of some areas, especially in the suburbs, will create new problems